Wearing Clio - The production of historical knowledge in Fashion (ModaPalavra e-periódico, 2014)
Study on the relationship between fashion and history, considering working with documents, made in sources of research historian from the goals that drive their approach and historiographical proposition. Propose means of historical production from the Fashion object in its different variations and contexts.
Keywords: history; research; fashion